2014
DOI: 10.1146/annurev-cellbio-101011-155831
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Polyadenylation Element Binding Proteins in Development, Health, and Disease

Abstract: The cytoplasmic polyadenylation element binding (CPEB) proteins are sequence-specific mRNA binding proteins that control translation in development, health, and disease. CPEB1, the founding member of this family, has become an important model for illustrating general principles of translational control by cytoplasmic polyadenylation in gametogenesis, cancer etiology, synaptic plasticity, learning, and memory. Although the biological functions of the other members of this protein family in vertebrates are just … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
216
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(221 citation statements)
references
References 146 publications
1
216
2
2
Order By: Relevance
“…Cytoplasmic polyadenylation of maternal mRNAs requires a cytoplasmic polyadenylation element (CPE) that binds specific trans-acting proteins (Pique et al, 2008). Studies in Xenopus and mouse oocytes found that the CPE-binding protein 1 (CPEB1) mediates cytoplasmic polyadenylation of many CPEcontaining mRNAs (Ivshina et al, 2014). During Xenopus oocyte maturation, phosphorylation of CPEB on several serine/threonine residues is required for early activation of a class of maternal mRNAs, while a large fraction (70-90%) of CPEB1 proteins undergo a polyubiquitylation-dependent degradation in meiosis I (Mendez et al, 2002;Setoyama et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cytoplasmic polyadenylation of maternal mRNAs requires a cytoplasmic polyadenylation element (CPE) that binds specific trans-acting proteins (Pique et al, 2008). Studies in Xenopus and mouse oocytes found that the CPE-binding protein 1 (CPEB1) mediates cytoplasmic polyadenylation of many CPEcontaining mRNAs (Ivshina et al, 2014). During Xenopus oocyte maturation, phosphorylation of CPEB on several serine/threonine residues is required for early activation of a class of maternal mRNAs, while a large fraction (70-90%) of CPEB1 proteins undergo a polyubiquitylation-dependent degradation in meiosis I (Mendez et al, 2002;Setoyama et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It regulates germ cell development, synaptic plasticity and cellular senescence; CREB1 is important for both meiotic progression and mitotic divisions (5,24). CPEB1 neutralizing antibody or dominant-negative mutant forms of this protein inhibit cell division (2,25).…”
Section: Cpeb1mentioning
confidence: 99%
“…Twist, a transcription factor, plays an important role in EMT and metastasis (35). CPEB1 interacts with Twist1 mRNA and down-regulates its expression; in the absence of CPEB1, Twist1 mRNA translation is elevated, which leads to EMT and metastasis (5,36). In addition, upon CPEB1 reduction, matrix metalloproteinase 9 (MMP-9) mRNA, which encodes a metastasis-promoting factor, undergoes poly(A) lengthening and enhanced translation (33).…”
Section: Cpeb1mentioning
confidence: 99%
See 2 more Smart Citations